The effect of region, yeast strain and ascorbic acid on the development of a sulphur-like aroma and on Sauvignon blanc wine quality - Swart, Ewarda (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc )--University of Stellenbosch, 2000.